NORMS AND NEW MEDIA AS NEW PILLARS OF NEW NETWORK TERRORISM - Ahmad Saifuddin (al-Balagh : Jurnal Dakwah dan Komunikasi, 2022)
Terrorism is a constant phenomenon. However, the pattern and style of terrorism have changed considerably since 2010. This paper uses a case-study approach to explore the factors that lead individuals to join terrorist groups today. Analysts have long focused on three factors that drove individuals to join terrorist groups: "needs, narratives, and networks," commonly referred to as the 3N. This paper identifies two more: norms and new media (2N). Now recruitment often occurs through social media. Besides that, this study found that people who adhere to good norms are vulnerable to being affected by terrorism. The results of this study indicate that not all terrorists have bad personalities.The results of this study inform the community that the internalization of values is accomplished not only by teaching goodness but also by directing goodness. In addition, this research has implications for enhancing the digital literacy abilities of the community.